PROFILE IGA (VCA-P18+EBNA1) AND VIRAL LOAD EBV DNA AS A RISK FACTOR AMONG RELATIVES OF NASOPHARYNX CARCINOMA PATIENT WITH EBV POSITIVE AT DR. WAHIDIN SUDIROHUSODO HOSPITAL IN MAKASSAR - Nova Audrey Luetta Pieter (TALENTA PUBLISHER, 2019)
Introduction: Nasopharyngeal carcinoma (NPC) is closely associated to viral infection, i.e. Epstein-Barr virus (EBV), about 90 % of the worldwide are infected with EBV at same point of their lives. This virus is highly oncogenic and easily transmitted via saliva. The high level of biomarker for EBV infection can become a risk factor for NPC in relative’s NPC patients. Therefore, EBV related biomarkers is needed to enable screening and detecting early diagnosis of NPC in endemic area. Objective: This study aims to analyze the role of IgA (VCA-p18+EBNA1) levels and viral load (VL) as screening tools for early detection in relatives of positive EBV NPC patients. Therefore, it can be used as predicted risk factor for NPC. Method: The method used in this study is cross-sectional with consecutive sampling of 50 relatives of NPC patients treated at the Dr. Wahidin Sudirohusodo Hospital from August 2012 to May 2013. Univariate and bivariate analysis and t-test are used to measure and to show the correlation of Ig A (VCA-p18+EBNA1) level and VL. Result: Results showed that 28 % of the NPC patients are female with an average age of 31.12±11.91. Sixty-eight percent of the relatives are siblings, and most of them are Buginese tribe (58%). According to the risk distribution of NPC, the sampling is grouped in 3 categories i.e. high risk, intermediate risk, and low risk to NPC. There is 50% of the relatives of the NPC patients categorized to the intermediate risk. The IgA (VCA-p18+EBNA1) level is significant (p=0.000) compared with the VL level (p=0.337). Sixteen percent of the high-risk group have a normal pattern, but it still needs high awareness. Statistically, the Pearson correlation analysis showed a relationship but not significant. Conclusion: It could be concluded that IgA (VCA-p18+EBNA1) and VL level could be used as a screening method and early detection in relatives of NPC patients and become a predicted risk factor for NPC